Otitis Media Module in the Pediatric Preclerkship Educational Exercises (PRECEDE) Curriculum - Cooper, Stacy (MedEdPORTAL, 2020)
INTRODUCTION: The Johns Hopkins Pediatrics Clerkship developed the PRECEDE (preclerkship educational exercises) curriculum with the primary goal of offering students formative instruction in essential pediatric clinical skills to prepare them for their clerkship. PRECEDE sessions occur at the beginning of each basic clerkship for new clinical clerkship students. The otitis media module is one in a series of modules presented in the curriculum and consists of a lecture and four short skills-development stations, each with a faculty facilitator. METHODS: This 2-hour module began with a 1-hour didactic overview of otitis media. Medical students were divided into three groups. One group learned about writing prescriptions via two otitis media clinical vignettes. Another group explored visualization and diagnosis of otitis media via video. The last student group was subdivided and learned proper techniques for positioning and restraining pediatric patients during otoscopic exams and the psychomotor skills for performing otoscopic examinations, including pneumatic otoscopy. Student groups rotated through all four activity stations. Students were guided through discussion to develop interpretation, diagnostic, and treatment skills for acute otitis media. RESULTS: Between 2010 and 2012, 254 third- and fourth-year medical students participated in this module. When asked to evaluate overall quality, 86% of learners rated the module as excellent, and 14% rated it as good. DISCUSSION: By establishing these important skills, students may be better equipped to develop appropriate otitis media assessments, diagnoses, and care plans for patients and to use otitis media as a platform for broad education in other essential pediatric skills.